Determination of Relationship between Infection and Serum Levels of Prohepcidin in Pediatric Patients before and after Bone Marrow Transplantation - GÖKER, BAHAR; GÖNÜL, ONUR (GEORG THIEME VERLAG KG, 2015)
Since the immune system is suppressed before bone marrow transplantation (BMT), severe infections might arise. This clinical article considers the role of prohepcidin, in addition to interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha) in infections occurring after BMT. Serum prohepcidin, IL-6, TNF-alpha, and C-reactive protein (CRP) levels were measured in 10 pediatric BMT patients by enzyme-linked immunosorbent assay before and after BMT. The results were evaluated statistically. As a result of the analysis, it was observed that there was a significant correlation between serum prohepcidin and IL-6, TNF-alpha, and CRP levels in the pretransplantation, posttransplantation, and discharge periods of the patients. The relationship between CRP levels and prohepcidin levels suggests that the serum prohepcidin level might be an important parameter for transplantation patients in consideration of infection. Verification of these results from future studies may confirm the clinical importance of hepcidin.
Keywords: bone marrow transplantation; hepcidin; prohepcidin